Metodologia numérica para determinação da vida em fadiga de juntas soldadas considerando tensões residuais na ZAC - Tremarin, Ronaldo Cesar (2022)
The present work aimed to test an alternative cementation for cement bases. paving. In this way, the development of a geopolymer with the properties necessary for application on cemented recycled bases. The constant concern about reducing the consumption of materials in infrastructure works, makes maintenance and reconstruction of pavements with the reuse of old material is in increasing development. The increase in cargo transported on Brazilian highways makes causing loads on the pavement to increase and require greater support capacity. In this context, the cementation of recycled material and reincorporation as a base and/or sub-base meets this need and, at the same time, mitigates the environmental liability of recycled material deposited in a dump, waiting or deposited on the side of the highway. The program experimental proposes the use of fly ash as a precursor material, hydroxide and silicate sodium as activators. The results present mechanical resistance values ​​that meet the minimum requirements required by DNIT for this type of material, and some mixtures obtained values ​​greater than 30MPa after 365 days of curing. At the end of work, durability and fatigue life assessments were carried out, where it was concluded that it is possible and technically viable to use alternative cements based on recycled deep restoration of floors.